Child survivors of the Holocaust in Greece : memory, testimony and subjectivity - Hantzaroula, Pothiti (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"A historical investigation of children's memory of the Holocaust in Greece illustrates that age, generation and geographical background shaped postwar Jewish identities. The examination of children's narratives deposited in the era of digital archives enables an understanding of the age-specific construction of the memory of genocide, which shakes established assumptions about the memory of the Holocaust. In the context of a globalized Holocaust memory established through testimony archives, the present research constructs a genealogy of the testimonial culture in Greece by framing the rich source of written and oral testimonies in the political discourses and public memory of the aftermath of the Second World War. The testimonies of former hidden children and child survivors of concentration camps illuminate the questions that haunted postwar attempts to reconstruct communities, related to the specific evolution of genocide in Greece and to the rising anti-Semitism of postwar Greece. As an oral history of child survivors of the Holocaust, the book will be of interest to researchers in the fields of the history of childhood, Jewish studies, memory studies, Holocaust and genocide studies"--
Meaning, Memory and Archive: The Politics of the Creation of Archival Material on the Holocaust -- The War Became Real -- Trajectories of Escape from the German Persecution of the population of Salonika and Athens -- Hidden Children in Volos: Trajectories and Identities -- Life and Memory of Concentration Camps: The Bergen Belsen Experience -- The Beginning of an Unknown Era: The Role of anti-Semitism in the Construction of Postwar Identities -- Remaking the Meaning of Living Entre Mozotros: Postwar Reconstruction of Jewish Communities -- Family Legacies: Memory, Postmemory and Transgenerational Haunting -- The Legacy of the Holocaust and Beyond.
OCLC-licensed vendor bibliographic record.
Keywords: Holocaust survivors -- Greece; Jewish children in the Holocaust -- Greece; Holocaust, Jewish (1939-1945) -- Greece; World War, 1939-1945 -- Atrocities -- Greece; Collective memory -- Greece; Jews -- Identity; Greece -- History -- Occupation, 1941-1944.; HISTORY / General; HISTORY / Europe / General; HISTORY / Europe / Western